Development of bimetallic Pd-Zn catalysts for methanol steam reforming: hydrogen production for fuel cells - Xalabile, Philasande (Centre for Catalysis Research, 2017)
Proton exchange membrane fuel cell (PEMFC) has been reported as clean and efficient energy technology from conversion of H₂. However, one of the main challenges remains the storage and transport of hydrogen. The promising alternative is to produce H₂ on site by a reformer using a H₂-dense liquid as a fuel, a technology known as fuel processing. Methanol is an attractive source of H₂ compared to other fuels as it presents several advantages, i.e. it is obtained sulphur-free, has a high H to C ratio and therefore produces a H₂-rich reformate, can be reformed at low temperatures (200 - 300°C) and is a liquid at ambient conditions so that it can be easily handled. Typically, Cu-based catalysts are used for steam reforming of methanol due to their high activity (i.e. H₂ production) and high selectivity towards CO₂. As CO poisons anodic catalyst of PEMFC, high selectivity towards CO₂ is crucial so as to eliminate or at least minimize CO removal load downstream a fuel processor. However, Cubased catalysts are thermally unstable and suffer deactivation due to sintering at high temperatures (> 250°C). Moreover, Cu-based catalysts are pyrophoric and therefore difficult to handle. Recent studies show that PdZn catalysts are very promising as they exhibit comparable activity and selectivity to Cu-based ones. Furthermore, PdZn catalysts are thermally stable in the typically methanol steam reforming temperature range (200 - 300°C). Most literature attributes high CO₂ selectivity of PdZn catalysts to formation of PdZn alloy. It is generally agreed that PdZn alloy is formed when PdZn catalysts are reduced in H₂ at high temperatures (> 250°C). In this work, a Pd/ZnO catalyst aimed at 2.5 wt% Pd was successfully prepared via incipient wetness impregnation and the duplicate preparation of the catalyst was successful. Both impregnation catalysts were confirmed by ICP-OES to contain similar weight Pd loadings i.e. 2.8 and 2.7 wt%, respectively. The actual Pd loading (ICP-OES) was slightly higher than the target loading (2.5 wt%) due to Pd content of Pd salt underestimated during catalyst preparation. Furthermore, crystallite size distribution, i.e. PdO crystallites on ZnO support, was similar (i.e. 6.7 ± 2.4 nm and 6.3 ± 1.9 nm) for both impregnation catalysts.